A case of crescentic glomerulonephritis with exacerbation of pre-existing IgA nephropathy after COVID-19 - Esra Karabağ Yılmaz; Seha Saygılı; Gülüstan Musayeva; Rüveyda Gülmez; Ayşe Ağbaş; Yasemin Özlük; Nur Canpolat (The Turkish Journal of Pediatrics)
Background. Relapses or new-onset IgA nephropathy (IgAN) have been documented in patients after vaccination against SARS-CoV-2; however, only one adult patient has been reported in whom pre-existing IgAN worsened during coronavirus disease 2019 (COVID-19).